Comparison of Streptokinase and Urokinase for Thrombolysis in Blocked Tunnel Cuffed Catheter Among the Patients of Chronic Renal Failure Undergoing Hemodialysis - Tahir, Taleah; Raja, Khalid Mehmood; Azam, Malik Nadeem; Arshad, Abdul Rehman; Mir, Abdul Wahab; ., Salahuddin (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the efficacy of Streptokinase and Urokinase for thrombolysis in blocked tunnel cuffed catheter among the patients with chronic renal failure undergoing hemodialysis. Study Design: Comparative prospective study. Place and Duration of Study: Department of nephrology Pak Emirates Military Hospital Rawalpindi Pakistan, from Aug 2019 to Mar 2020. Methodology: A total of 100 cases were included in the study which was undergoing hemodialysis in the nephrology department and had a poorly functioning or blocked tunnel cuffed catheter. These patients were either given Urokinase or Streptokinase in standard doses for thrombolysis. The lottery method was used to designate the patient either in the Streptokinase or Urokinase groups. The primary endpoint was the resolution of blocking and regain of proper functioning of the catheter. Results: In our study, 54 (54%) patients were males, and 46 (46%) were females. The mean age of the study participants was 44.63 ± 3.782 years, and the mean duration of chronic kidney disease was 2.19 ± 6.814 years. 43 (43%) patients were given Urokinase, while 57 (57%) were given Streptokinase. After applying the logistic regression, we found that the use of Streptokinase had a significant association with the resolution of blocking and regain of proper functioning of the catheter compared to the use of Urokinase. Conclusion: This study concluded that most catheters regain the proper functioning after thrombolysis with either Urokinase or Streptokinase. However, Streptokinase emerged as a better agent for this purpose in our study.